Quality Of Public Services At The Population And Civil Registration Services Indragiri Hulu District - Ningsih, Fitria; Afriaris, Said (AGUSPATI Research Institute, 2019)
This study was conducted to determine the quality of public services at the Department of Population and Civil Registration of Indragiri Hulu Regenc, which includes services for making Identity Cards (KTP), Family Cards (KK). The method used in this research is descriptive qualitative research. Based on observations made by researchers conducting interviews and getting direct information through several office service employees and service users. The data collection techniques are observation, interview, and documentation techniques. Supporting informants are service employees at the Department of Population and Civil Registration of Indragiri Hulu Regency and service users. This study uses data analysis techniques consisting of data reduction, data presentation, and drawing conclusions from the research results. The targeted outputs in this study indicate that the implementation of the quality of public services at the Population and Civil Registration Office of Indragiri Hulu Regency are: (1) Tangible evidence regarding service facilities and infrastructure for the convenience of the community. (2) Aspects of employee reliability in handling any complaints about the service process for making e-KTP, Birth Certificates and Family Cards. (3) Aspects of responsiveness (responsiveness) of employees with the community at the time of service. (4) Assurance, there is a consistent problem of timeliness in the implementation of services. (5) Dimensions of Empathy (empathy) which shows the attitude of employees who are friendly, smiling, non-discriminatory and respecting the community as service users. The absence (discrimination) of service differences in management, thus showing quality by giving a pleasant impression in the service process in accordance with community expectations.